The Phenomenon of the Impact of Online Games in News Coverage on Metro TV’s Instagram: A Voyant Tools Analysis - Siti Apriani; Arianto; Alem Febri Sonni (LONTAR: Jurnal Ilmu Komunikasi, 2025)
This study examines the social discourse surrounding the impact of online gaming using Metro TV’s Instagram news posts as the primary data source. Employing a qualitative phenomenological approach supported by Voyant Tools, the research identifies dominant lexical patterns and relational structures within public commentary. Word cloud analysis highlights “game” and “online” as the most frequent terms, indicating that online gaming constitutes the core focus of public concern. Additional prominent terms such as “judol,” “judi,” and “bocah” reveal strong associations between online gaming, online gambling, and youth involvement. Trend analysis further demonstrates fluctuating frequencies of key terms “online game,” “online judi,” and “online online” suggesting shifting narrative emphasis across document segments. Network analysis shows close lexical associations among “game,” “online,” “judol,” and “judi,” reflecting public perceptions that link gaming activity with financial risk and deviant behaviors. Collectively, these findings demonstrate that online gaming is viewed not merely as a digital entertainment activity but as a multidimensional social issue intertwined with gambling practices, economic vulnerability, and concerns for adolescent well-being.